Protective effect and mechanism of Sufentanil on acute lung injury in septic mice - Hongqiao Hou; Bowen Jiang; Aiqing Zhu; Junjun Hou; Zhe Qu; Ruping Liu; Aiqun Li (Frontiers in Pharmacology)
This study was designed to investigate the protective effect and mechanism of Sufentanil on acute lung injury in septic mice based on network pharmacology and animal experiments, and to provide new ideas for clinical treatment. To this end, a protein-protein interaction (PPI) network for common targets was first constructed with Swiss Target Prediction Database, GeneCards Database, Draw Venn Diagram Software, STRING 11.5 Database, Cytoscape 3.10.0 Software and Metascape Database, and then key targets were subject to enrichment analysis by Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) to obtain the key targets of Sufentanil for the treatment of pulmonary sepsis, and then verified by animal experiments. A sepsis model was constructed by cecal ligation and puncture (CLP) in this study, and lung tissues and bronchoalveolar lavage fluid (BALF) were taken from each group of mice. The morphological changes of lung tissues and apoptosis were observed by HE and TUNEL staining, the content of inflammatory factors in the lung tissues was detected by ELISA, and the expression of proteins, such as p-JAK2 and p-STAT3, was detected in the lung tissues by Western blotting. According to the results of network pharmacology, a total of 40 common targets of were screened out for Sufentanil and pulmonary sepsis, and GO enrichment analysis involved 1,483 biological processes (BPs), 84 cellular components (CCs) and 125 molecular functions (MFs); KEGG enrichment analysis identified 137 signaling pathways with p < 0.05 such as JAK-STAT. According to the results of animal experiments, compared with the control group, mice in the model group had severe lung tissue injury and elevated expression of relevant inflammatory factors in lung tissue. Compared with the model group, CLP + Sufentanil group showed reduced pathomorphologic lesions, lower expression of inflammatory factors and apoptosis level, as well as lower expression of p-JAK2 and p-STAT3 proteins in lung tissue. The results of animal experiments were consistent with network pharmacology. In summary, Sufentanil may improve lung injury in septic mice by inhibiting the JAK2-STAT3 signaling pathway, which provides a basis for research on the mechanism of Sufentanil on pulmonary sepsis and clinical treatment.